Italʹianskii Tamizdat, or Publishing Uncensored Soviet Literature in Italy: Editorial Policies of Mondadori and Il Saggiatore (1967–1991) - Sicari, Ilaria (Wiener Slawistischer Almanach, 2024)
During the Cultural Cold War, Italy was amongst the European countries where the publication of uncensored Soviet literature (nepodtsenzurnaia literatura) flourished the most. The Italian publishing houses Mondadori and Il Saggiatore significantly contributed to the cross-border production and diffusion of tamizdat – Soviet and Eastern European texts that, uncensored and/or unpublished in the Eastern bloc, were smuggled out and published in the West. With the aim to illustrate the editorial policies of Western publishing houses involved in the transnational socialization of this particular kind of socially and ideologically connotated cultural object, I analyze a corpus of archival documents (readers’ opinions, editorial correspondence, reviews, editorial assessments, etc.) to highlight the criteria that have determined the selection or rejection of clandestine Russian manuscripts by Mondadori and Il Saggiatore. Through the reconstruction of the microhistory of several tamizdat editions, I aim to assess the agency of these publishing houses, and thereby to contribute to a broader understanding of cultural production and book diplomacy during the Cold War.